2009
DOI: 10.1111/j.1538-7836.2009.03521.x
|View full text |Cite
|
Sign up to set email alerts
|

Human alternatively spliced tissue factor is not secreted and does not trigger coagulation

Abstract: 1-74) in patients (n = 68) with normal MP-TF activity (P = 0.028). In the group of 51 patients who presented with VTE, survival was significantly worse in patients with elevated MP-TF activity than in those with normal MP-TF activity (P = 0.010). In univariate analysis only tumour type, thrombosis and MP-TF activity were significantly associated with survival. In multivariate analysis, adjustment for tumour type, age and stage, did not affect the association between MP-TF activity and mortality (P < 0.015).The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 14 publications
(36 reference statements)
1
14
0
Order By: Relevance
“…Western blot analysis on MVs and supernatants revealed that asTF is not secreted from non-activated endothelial cells (data not shown). Also, stimulation of HUVEC cells with IL-1α did not result in asTF secretion, as previously reported by Böing et al [18]. However, other studies that utilized endothelial or malignant cell lines were able to demonstrate asTF in conditioned media and/or plasma of cancer patients [14,29].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Western blot analysis on MVs and supernatants revealed that asTF is not secreted from non-activated endothelial cells (data not shown). Also, stimulation of HUVEC cells with IL-1α did not result in asTF secretion, as previously reported by Böing et al [18]. However, other studies that utilized endothelial or malignant cell lines were able to demonstrate asTF in conditioned media and/or plasma of cancer patients [14,29].…”
Section: Discussionsupporting
confidence: 77%
“…Even though asTF promotes cancer progression non-proteolytically, coagulant properties of asTF and thus its involvement in thrombosis and/or hemostasis are controversial [1820]. Both flTF and asTF accumulate in occlusive thrombi [21], suggesting a role for asTF in thrombus formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the level of asTF in human plasma may be substantial, amounting to 10 -30% of total TF (107), the question of whether it contributes to coagulation is a matter of debate. Several observations suggest that asTF has a role in hemostasis: 1) asTF localizes on platelet surfaces in experimental blood clots; 2) the 165-166 lysine doublet involved in FVIIa binding is maintained in asTF, and theoretically, activity of the TF/FVIIa complex is maintained; 3) when added to plasma in vitro, asTF shortens the clotting time (31); and 4) while cell-expressed asTF alone does not appear to have procoagulant properties (32,47), endothelial asTF expression in the presence of TF may be procoagulant, as depletion of asTF reduced TFdependent coagulant activity (285). Thus asTF and flTF may cooperate in a synergistic fashion (FIGURE 2D), but such a mechanism, as well as how asTF would enhance function of normally spliced TF, remains speculative.…”
Section: Alternatively Spliced Tfmentioning
confidence: 99%
“…It is controversial whether asTF exhibits procoagulant activity [1], [3], [4], [5]. Although asTF lacks important residues that in flTF interact with macromolecular substrate, the majority of residues interacting with FVII(a) are present in flTF and asTF [6].…”
Section: Introductionmentioning
confidence: 99%